2022
DOI: 10.1155/2022/5530188
|View full text |Cite
|
Sign up to set email alerts
|

Main Applications and Recent Research Progresses of Additive Manufacturing in Dentistry

Abstract: In recent ten years, with the fast development of digital and engineering manufacturing technology, additive manufacturing has already been more and more widely used in the field of dentistry, from the first personalized surgical guides to the latest personalized restoration crowns and root implants. In particular, the bioprinting of teeth and tissue is of great potential to realize organ regeneration and finally improve the life quality. In this review paper, we firstly presented the workflow of additive manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 198 publications
1
14
0
Order By: Relevance
“…Therefore, DLP is advantageous for rapid printing of larger parts with fewer details, while SLA is superior for printing accurate parts with intricate details (Huang et al, 2022).…”
Section: Stereolithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, DLP is advantageous for rapid printing of larger parts with fewer details, while SLA is superior for printing accurate parts with intricate details (Huang et al, 2022).…”
Section: Stereolithographymentioning
confidence: 99%
“…In implant dentistry, applications of and research into AM are becoming increasingly extensive, ranging from fabrication of surgical guides and dental implants to dental casts and implant frameworks, among other items. The use of AM has led to a progression of implant dentistry applications from traditional, purely empirical methods to more accurate digital medicine (Schweiger et al, 2021;Huang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these reviews highlighted above, trends in reported challenges and areas of opportunity have emerged. The area of focus here will be on the following two general challenges that remain in adoption of ceramic AM; Limited mechanical strength due to either: low density, processing defects (e.g., interlayer delamination), and/or material composition limitations in existing well‐developed feedstock 1,3,4,16,27,38,49,56,65,67–69,71,72,74,75,79,90,94,112,123,128,145 156 Poor identification and quantification of defects and limited standardization and speed of advancements the processes (feedstock development, processing parameters, postprocessing steps, etc.…”
Section: Challenges and Opportunities In Ceramic Ammentioning
confidence: 99%
“…In order to assess and analyze recent review articles in this area, a Scopus search was conducted in April 2023 for the specific time frame of 2018–2023. This search resulted in 165 review articles on ceramic additive manufacturing or some subset of that topic 1,3–166 . Figure 1 shows a graphical representation of the number of review articles separated into five focus areas.…”
Section: Introductionmentioning
confidence: 99%
“…e usage of modern manufacturing methods made the researchers to look into the past techniques, like as such as subperiosteal implants, and re-explain them in a modern and digital way [31,32]. is can be extremely useful in the case of severe bone atrophy, which does not allow for the placement of end osseous dental implants if a regenerative intervention approach is not followed, particularly in the case of elderly patients with limited financial resources and who do not wish to undergo long and complex regenerative surgeries prior to the insertion of end bony dental implants [33].…”
Section: Introductionmentioning
confidence: 99%